REFUSAL AND ACCEPTANCE STRATEGIES REALIZATION IN SUNDANESE CONTEXT - Sartin T. Miolo; Emzir Emzir; Asep Supriadi (Indonesian EFL Journal, 2018)
This study investigates the refusal and acceptance strategies realization in sundanese context among students of a private university in Kuningan. The study is purposely designed to investigate the types of refusal and acceptance strategies used in Sundanese context. This study employed a qualitative method as a research design. A Discourse Completion Task (DCT) was used to collect the data which was spread into 30 respondents. The questionnaire was in Bahasa Sunda because the respondents were Sundanese people, so it can be easier to be analyzed. The findings showed that there were 240 utterances consisted of 150 utterances of refusal and 90 utterances of acceptance. The refusal strategies consisted of 12 strategies and the acceptance strategies consisted of 6 strategies. Most of the respondents which are Sundanese are polite as it can be seen from their responses when they were asked to accompany their lecturer or when they refused to the person with higher power. They always say punten, hapunten sateuacana or it can be called ‘sorry’. The term ‘sorry’ showed that they try to be polite when talking with the higher power and distance. Yet, they use different talking when they talk to their friends who have the same power. So, they can place where they should be polite and to whom they talk.    Keyword: acceptance strategy, refusal strategy, sundanese culture.